Overview of Nutritional Status in Pulmonary Tuberculosis Patients Undergoing Outpatient Treatment at Tk.II Iskandar Muda Hospital Banda Aceh - Safitri, Rosi Mega; Kurniawan, Hendra; Nauval, Iflan; Ko Ko Htet, Kyaw (Universitas Nahdlatul Ulama Surabaya, 2024)
Tuberculosis (TB), caused by Mycobacterium Tuberculosis (MTB) and transmitted through the air, primarily affects the lungs. In Aceh Province, the reported TB cases reached 41,596. Nutritional status is a pivotal factor influencing TB occurrence, as malnutrition can compromise immune function, increasing susceptibility to MTB. This study assesses TB patients' nutritional status based on BMI, malnutrition risk, and body weight changes during therapy. As quantitative research with a descriptive cross- sectional study design, the study used the medical records of outpatient pulmonary TB patients at the Pulmonary & TB-DOTS Polyclinic of TK—II Iskandar Muda Banda Aceh Hospital, who underwent intensive phase therapy from January to December 2023. Malnutrition risk screening utilizes the Malnutrition Universal Screening Tools (MUST) instrument. The study revealed a high prevalence of pulmonary TB cases, particularly among individuals aged 17-25. Based on the MUST instrument, patients over 60 showed a high risk of malnutrition, with the average patient having a MUST score of 3 (indicating high risk). Most patients experienced a significant increase in body weight during the intensive treatment stage. Weight gain significantly contributes to the success of tuberculosis treatment, influencing positive changes in the nutritional status of pulmonary tuberculosis patients.